1996
DOI: 10.1007/bf00197579
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional regulation of hydroxypyruvate reductase gene expression by cytokinin in etiolated pumpkin cotyledons

Abstract: To understand the mechanisms by which the expression of a specific gene is modulated by cytokinin, the regulation of hydroxypyruvate reductase (HPR) transcript levels by N6-benzyladenine (BA) in etiolated pumpkin (Cucurbita pepo L. cv. Halloween) cotyledons was investigated. A pumpkin HPR cDNA was generated by reverse transcriptase-polymerase chain reaction and its nucleotide sequence was determined. An antisense HPR RNA was prepared for RNase protection analysis of HPR-mRNA expression patterns in the cotyledo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

1997
1997
2009
2009

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…There is an increasing body of information on cytokininresponsive genes in higher plants, but genes that are known to be regulated at the transcriptional level are currently limited. These include genes for msr1 (pLS216) (Dominov et al, 1992), hydroxypyruvate reductase (Andersen et al, 1996), chalcone synthase and dihydroflavonol reductase (Deikman and Ulrich, 1995), and C4Ppc1 (Suzuki et al, 1994). Our results clearly demonstrate that ZmCip1 is a cytokinin-inducible gene that is expressed dosedependently at physiological concentrations, requiring no protein synthesis.…”
Section: Discussionmentioning
confidence: 60%
“…There is an increasing body of information on cytokininresponsive genes in higher plants, but genes that are known to be regulated at the transcriptional level are currently limited. These include genes for msr1 (pLS216) (Dominov et al, 1992), hydroxypyruvate reductase (Andersen et al, 1996), chalcone synthase and dihydroflavonol reductase (Deikman and Ulrich, 1995), and C4Ppc1 (Suzuki et al, 1994). Our results clearly demonstrate that ZmCip1 is a cytokinin-inducible gene that is expressed dosedependently at physiological concentrations, requiring no protein synthesis.…”
Section: Discussionmentioning
confidence: 60%
“…Cytokinins also regulate the expression of NADH-HPR gene by acting at the level of transcription and posttranscriptionally. Light is a major factor in the induction of NADH-HPR protein synthesis and the dark causes a strong reduction in its level (Andersen et al 1996). Probably, for this reason the reaction of reduction of hydroxypyruvate to glycerate in dark-grown Chlorella vulgaris is very low.…”
Section: Discussionmentioning
confidence: 98%
“…However, the abundance of the large subunit of Rubisco did not vary appreciably upon cytokinin treatment in our present study, demonstrating once more that transcript amounts do not necessarily reflect protein amounts. Andersen et al (1996) suggested a transcriptional regulation of specific nuclear genes by cytokinin in etiolated, excised Cucurbita cotyledons, whereas Kusnetsov et al (1994) suggested a cytokinin action at the post-transcriptional level in excised Lupinus cotyledons. By analogy to blue-light signal transduction (Reymond et al 1992), this regulation may involve protein phosphorylation, especially as this type of modification is functional in PSII assembly (Allen and Staehelin 1994).…”
Section: Exogenous Cytokinin Cures a Developmental Moss Mutantmentioning
confidence: 96%